A systematic review of economic evaluations of the use of memantine alone or combined with donepezil for moderate to severe Alzheimer’s disease - Oliveira,Ione Ayala Gualandi de (2019)
Abstract Objective: To synthesize the available evidence and state of the art of economic evaluations which evaluate the use of memantine, whether alone or combined with donepezil, for moderate to severe Alzheimer’s disease (AD), focusing on the analytical decision models built. Method: The electronic databases MEDLINE, EMBASE, NHS EED, CEA Registry and LILACS were searched for references. After duplicates were removed, two independent reviewers evaluated the titles and abstracts and subsequently the full texts. The Drummond M. tool was used to evaluate the quality of the studies. Results: After the application of the eligibility criteria, twelve complete economic evaluations were included. One evaluation was a clinical trial, two involved simulations and nine used Markov models. The main outcome measure adopted was dominated by cost per quality adjusted life year (QALY). The use of memantine was considered cost-effective and dominant in eight studies; while in a single study, its use was dominated when compared to donepezil for moderate AD. Sensitivity analyzes were systematically performed, with robust results. The quality assessment indicated that the methodological quality of the studies was good. Conclusion: Although there is some controversy regarding the benefits derived from the use of memantine, whether combined or not with donepezil, the evidence collected suggests that it is cost-effective in the countries where the studies were performed. However, local economic studies need to be performed, given the significant variability derived from the different parameters adopted in the evaluations.